2021
DOI: 10.1155/2021/4520571
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Determination of Bridge Prestress Loss under Fatigue Load Based on PSO‐BP Neural Network

Abstract: During the service period of a prestressed concrete bridge, as the number of cyclic loads increases, cumulative fatigue damage and prestress loss will occur inside the structure, which will affect the safety, durability, and service life of the structure. Based on this, this paper studies the loss of bridge prestress under fatigue load. First, the relationship between the prestress loss of the prestressed tendons and the residual deflection of the test beam is analyzed. Based on the test results and the main i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In terms of the abovementioned structures, the value of efective prestress during service plays a crucial role in their security state. However, the prestress losses due to concrete shrinkage and creep [6,7], duct friction [8], relaxation of steel strands [9], corrosion [10], and other external efects [11] are unavoidable. Once the efective prestress is reduced to a certain threshold, the structural performance can be signifcantly degraded and may even lead to structural damage [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the abovementioned structures, the value of efective prestress during service plays a crucial role in their security state. However, the prestress losses due to concrete shrinkage and creep [6,7], duct friction [8], relaxation of steel strands [9], corrosion [10], and other external efects [11] are unavoidable. Once the efective prestress is reduced to a certain threshold, the structural performance can be signifcantly degraded and may even lead to structural damage [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%